Analysis of Conversational Implicature Found in the Silence of the Lambs Movie - Pinayungan, Anggi Lastri; Lastri Wahyuni Manurung; Carolina Pakpahan (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
This research employs a descriptive qualitative approach to examine Conversational Implicatures found in "The Silence of the Lambs" Movie using Grice's Cooperative Principle theory (1975). The objective of the study is to identify the prevalent type of Conversational Implicature and characterize its pattern of usage. The results indicate that Generalized Conversational Implicature (GCI) accounts for 42.2% of the total implicatures, while Particularized Conversational Implicature (PCI) represents 57.8%. Notably, Particularized Conversational Implicature emerges as the dominant type. The patterns identified within Generalized Conversational Implicature (GCI) are (1) conveying additional messages without needing to explain in detail or explicitly,(2) responses that do not require additional explanation, and (3) brief and succinct responses. However, Particularized Conversational Implicature patterns generated are (1) based on the specific context of the situation, (2) based on specific knowledge of the case and the context of the conversation, (3) use of cryptic language and allusions, (4) manipulation of hearing sympathy or understanding by sharing personal desires,(5) the psychological dynamics between the characters,(6) use of indirect questions.